Curcumin as a Potential Candidate for Patients with COVID-19 Infection and Diabetes: A Review - Shojapour, Mana; Hosseinikhah, Seyedeh Maryam; Sohrab, Mehrnoush; Aliabadi, Parastoo Karimi; Kashi, Zahra; Jamialahmadi, Tannaz; Hosseini-Khah, Zahra; Sahebkar, Amirhossein (Coronaviruses, 2025)
COVID-19 causes a range of illnesses, from mild symptoms resembling the common cold to severe pulmonary damage leading to Acute Respiratory Distress Syndrome (ARDS). Researchers worldwide are actively searching for the most effective medications with minimal side effects for treating COVID-19. This review aimed to discuss the therapeutic potential of Curcumin (CUR) in managing COVID-19 infection in patients with comorbidities, such as Diabetes Mellitus (DM), as well as the underlying mechanisms of action responsible for CUR's anti-inflammatory and immunomodulatory effects. Given the natural origin and fewer adverse effects of herbal and medicinal plants, many researchers have turned their attention to exploring their therapeutic properties. Turmeric, the main source of polyphenol CUR, has long been recognized for its beneficial pharmacological effects in traditional Ayurveda medicine in China and has recently gained attention from scientists. The study reviewed various types of studies investigating the antiviral activity of CUR. Among the 16 studies reviewed, 4 were computational studies, 2 were in vitro studies, and the remaining 10 were clinical trials. Among the 10 recent studies, 4 studies focused on patients with COVID-19 who had diabetes as an underlying condition. The findings from these studies suggested that CUR is a safe and pleiotropic molecule with multiple effects on intracellular signaling pathways, including alterations in cell growth, apoptosis, inflammation, and oxidation.
Keywords: COVID-19